DESAIN UJI COBA E-MAGAZINE DENGAN PENDEKATAN SOCIAL EMOTIONAL LEARNING (SEL) MENGGUNAKAN SOFTWARE KVISOFT FLIPBOOK PADA MATERI ASAM BASA - Abdillah Nur Fitriana; Yenni Kurniawati (UIN AR-RANIRY, 2020)
This research was instigated by the development of 4.0 industrial revolution era and the need of a teaching material to increase student character based on 2013 Curriculum. Therefore, it was designed a design and test of E-Magazine teaching material with Social Emotional Learning (SEL) approach using Kvisof Flipbook software on Acid Base lesson. It was Research and Development (R&D) using Borg & Gall procedure design. It was conducted at Private Islamic Integrated Senior High School Bangkinang. The subjects of this research were the experts of media design and learning material, practicality by Chemistry subject teachers and students. The object of this research was E-Magazine teaching material with SEL approach on Acid Base lesson. The data taken in this research were in the form of validity and response questionnaire data. The collected data were analyzed by using Qualitative and Quantitative Descriptive analyses. The developed E-Magazine was tested very valid with 90.52% percentage by the experts of media and material, practicality assessment was 81.45% by Chemistry subject teachers and it got very good response with 90% percentage from the students. Based on the result, it could be concluded that E-Magazine teaching material with SEL approach using Kvisof Flipbook software on Acid Base lesson was valid and good.